THE WASTE MANAGEMENT AND GOVERNMENT POLICY IN MANAGING POST-TRAIL WASTE - Fitri Nurhidayanti; Desriadi; Hamida; Hendri Pratama; Hera Viqulu Hani (Yayasan Wayan Marwan Pulungan, 2024)
Handling post-Pacu Lintas waste involves adequate government strategies and policies to overcome the environmental impacts produced by this event. This article investigates waste management after the Pacu Lane event and government policies implemented in waste management. By taking examples of experiences in several regions, this research analyzes the challenges and opportunities in post-Pacu Lane waste management as well as the policies implemented by the local government. Post-Pacu Lane waste management requires a holistic approach that involves community participation, the application of environmentally friendly technology, and policies that support recycling. This study also evaluates the positive and negative impacts of existing policies and explores innovations that can be implemented to increase the efficiency of waste management after the Pacu Lane event. The results of this research can provide insight into how the government can optimize waste management efforts after traditional cultural events such as Pacu Lane. It is hoped that the implications of these findings can help policymakers and practitioners in designing more effective and sustainable strategies for facing the challenges of waste management after cultural events in the future.